Manufacturing processes, ceramics - Gregor, Thomas G. (Englewood Cliffs, N.J. : Prentice-Hall, 1976)
An introduction to ceramic materials and the wide and varied uses of ceramic products, describing the techniques to form, dry, fire, decorate, and finish them.
Includes index.
Keywords: Ceramics -- Juvenile literature; Ceramics